Association Between Depression Severity and Ovarian Cancer Among American Women: A Cross-Sectional Study - Yang L; Zhang S; Li Y; Qian H; Xu W; Yu J (International Journal of Women's Health)
Li Yang,1,* Shuang Zhang,1,* Yajun Li,2 Haiqing Qian,3 Wenting Xu,3 Jinfen Yu1 1Department of Obstetrics and Gynaecology, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, Jiangsu, People’s Republic of China; 2Department of Orthopedics, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, Jiangsu, People’s Republic of China; 3Department of Reproduction, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinfen Yu, Email zjgzy005@njucm.edu.cn Wenting Xu, Email zjgzyxwt@njucm.edu.cnObjective: Inflammation is one of the main causes of ovarian cancer. Depression leads to an increase in pro-inflammatory cytokines, which in turn affects the progression and severity of cancer. There is a lack of research on the relationship between depression severity and ovarian cancer. This study aimed to explore the relationship between depression severity and ovarian cancer.Methods: The study used data from seven cycles of the National Health and Nutrition Examination Survey (NHANES, 2005– 2018). Weighted multivariable logistic regression models were used to analyze the association between depression severity and ovarian cancer.Results: A total of 14,843 women without cancer and 56 women only with ovarian cancer were included in this study. Weighted multivariable logistic regression models showed that severe depression was associated with ovarian cancer (unadjusted model, OR: 4.94, 95% CI: 1.14, 21.35, p < 0.05, p for trend: 0.1; partially adjusted model, OR: 6.10, 95% CI: 1.35, 27.51, p < 0.05, p for trend: 0.04; fully adjusted model, OR: 5.82, 95% CI: 1.19, 28.52, p < 0.05, p for trend: 0.05).Conclusion: Severe depression was positively correlated with ovarian cancer. Longitudinal studies are necessary to explore causality.Keywords: ovarian cancer, depression severity, cross-sectional study, NHANES, PHQ-9